Effects of Several Organic Fertilizers on Heavy Metal Passivation in Cd-Contaminated Gray-Purple Soil - Wang, Luyao; Liu, Siqi; Li, Jianfeng; Li, Shunqi (Frontiers in Environmental Science, 2022)
In order to explore the passivation effect and influence mechanism of different organic fertilizers on Cd in purple soil, the complete combination design was used to compare the effects of five organic fertilizers (nutshell organic fertilizer (NOF), pig manure organic fertilizer (PMOF), sludge organic fertilizer (SOF), humus soil organic fertilizer (HSOF) and earthworm soil organic fertilizer(ESOF) ) on available Cd in soil with different pollution levels at different dosages, and the relationship between the change of available Cd in soil and the transformation of Cd forms was discussed. The results showed that all kinds of organic fertilizers could effectively reduce the effectiveness of Cd in moderate and severe Cd-contaminated soil to achieve the purpose of passivation, and the passivation effect increased with the increase of organic fertilizer application rate, and the effective Cd content decreased by 9.09%~47.27% compared with the control. However, in mild Cd-contaminated soil, organic fertilizer could only reduce the effective Cd content under high dosage (8 g/kg). After the addition of organic fertilizer, the content of available Cd in soil decreased first and then increased over time, reaching the lowest value at 15 d and tended to be stable after 60 d. The change dynamics were consistent with the transformation dynamics of Cd forms. In addition, the results of Cd morphological correlation analysis showed that Exe-Cd and FeMnOx-Cd in soil had significantly positive contributions to available Cd, while Res-Cd showed significantly negative contributions. Organic fertilizer significantly reduced the contents of Exe-Cd and FeMnOx-Cd by increasing Res-Cd content, which significantly reduced the availability of Cd in soil.